Synthesis, characterization and acute toxicity of new Schiff base derived from phenylethyl amine and 2-hydroxy naphthaldehyde - Hatim, Ibtihal Hassan; Al-Masoudi, Wasfi Aboud; Ghadhban, Rashad Fadhil (European Journal of Chemistry, 2019)
There is an urgent need for the design and development of new and safer drugs, this has attracted organic chemists to synthesize new compounds with potential of biological and chemotherapeutic activities. Here we report, the condensation of phenylethylamine with 2-hydroxy naphthaldehyde yielded Schiff base derivative in good yield. Characterization of synthesized compound was carried by elemental analysis, IR, 1H-, 13C- and HSQC-NMR spectroscopy. The toxicity of the synthesized compound was determined using Balb/c mice model. Dixon’s up and down method was found to have an LD50 of 827.2 mg/kg of body weight, moderate toxicity.